Beyond Binary Measures: Introducing A Safety Net Hospital Index - Fredric Blavin; Avani Pugazhendhi; Stephen Zuckerman; John Holahan (Health Affairs Scholar, 2026)
Abstract Introduction Safety net hospitals (SNHs) disproportionately serve uninsured, Medicaid, and low-income Medicare patients, yet no universally accepted SNH definition exists. Existing binary measures frequently identify divergent hospital sets, creating research inconsistency and risking misaligned policy protections, concerns heightened by recent federal Medicaid cuts and site-neutral payment reforms. Methods Using Medicare cost report data for community hospitals, we introduce and validate a continuous, multidimensional SNH Index constructed as composite of Medicaid revenue share, uncompensated care burden, and low-income Medicare share. Results Hospitals in the highest SNH Index quartile had substantially lower operating margins (−2.0% vs. 3.1% in the lowest quartile), fewer days cash on hand (91 vs. 158 days), and higher rates of financial distress (36% vs. 21%). The SNH Index showed stronger correlations with financial performance than five binary SNH definitions and a proxy for MACPAC's Medicare Safety Net Hospital Index. Within each quartile, system-affiliated hospitals significantly outperformed independent hospitals financially. Conclusion These findings suggest that policies protecting SNHs should incorporate composite, burden-based measures, and account for system-level financial resources rather than relying on binary classifications alone.